Study of the paraffin crystallisation phenomena in the fluid dynamic behaviour of paraffinic crude oils - Phase 1 - Rodríguez, L.; Castañeda, M. (CT&F - Ciencia, Tecnología y Futuro, 2001)
The results obtained by relating the formation of wax crystals using traditional measurements such as cloud point, pour point and viscosity show the importance of analyzing the interactions among the chemical nature of crude oils, the physical-chemical variables and the fluid dynamics that cause different shapes and rates of crystallization. In addition, the specific value of viscosity should be measured at a certain temperature, as well as the rheological behavior of the crude oils during the process of formation and destruction of crystals due to shear rate. In order to carry out this study, a group of waxy crude oils was chosen. They were characterized considering the parameters mentioned above, and they were subjected to different cooling rates to microscopically observe the resulting morphologies, and to relate them to rheological behavior in a range of similar conditions that are obtained during hydrocarbon transport through pipelines. For this effect, laboratory tests were carried out, in addition to the scaling of results at the pilot plant level in a simulator to analyze the behavior of the fluids in dynamic or static conditions, in relation to prolonged pipeline downtime. This type of studies improves operational safety, offers considerable savings on additives, power, an increase in pumping capacity, and it also facilitates the selection of the most appropriate technology to control wax deposition.